(untitled) (Revista Electrónica REDINE, 2018)
Socioepistemology, is a proposal that part of meaningful learning and focuses on human formation holistic, integrating theory with practice in the various activities; It promotes continuity between all educational levels and between these and the socio- cultural processes. Values are a quality of being, the inspiring element of human knowledge, lines behavioral engineering life. These arise from experience and can be modified by the passage of time. Educating in values does not mean only to preach or values, but join them to the educational practice. In such sense the teacher of mathematics not only it has the task to transmit to their students knowledge and math skills, develop them gradually and them they can use in life, but also provide them with a comprehensive training that allows them to be critical of his own actions and others which will allow you to make the right decisions.